PERAN BUDAYA SEKOLAH DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SEKOLAH DASAR PESANTREN ASSHIDDIQIYAH - Khaulani, Qisti; Nulhakim, Lukman; Syachruroji, A.; Taufik, M. (STKIP Persada Khatulistiwa Sintang, 2025)
Character education is essential for developing students’ personalities, particularly religious character, which serves as a core value in strengthening student character education guidelines. In this regard, schools play a vital role in shaping students’ religious character. One way to achieve educational goals with strong character is through the optimal implementation of school culture. This study aims to describe the process of school culture in shaping students’ religious character, to identify the religious character of students, and to analyze the role of school culture in developing religious character among students at Asshiddiqiyah Islamic Boarding School Elementary School. This research employed a qualitative method with a descriptive approach. The participants consisted of five informants, including the principal, the first- and fifth-grade homeroom teachers, and two tahfidz (Qur’an memorization) teachers for grades 1 and 5. Data were collected through overt and covert observations, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman (1984) model, including data reduction, data display, and conclusion drawing or verification. The findings indicate that the habituation of school culture—such as the culture of reading the Qur’an, congregational prayer, and greeting—plays a significant role in shaping students’ religious character at Asshiddiqiyah Islamic Boarding School Elementary School.